The Optical Appearance of Compact Stars: Shadows and Luminous Rings - Guerrero, Merce (Gravity, Cosmology, and Astrophysics, 2023)
In 2019, the direct imaging of M87* [1] by the Event Horizon Telescope opened the door to understand the nature of the central object and the underlying theory of gravity, since it explore the regions where the gravitational field is extremely strong. In the images obtained by the collaboration, we can observe two distinct regions: a dark circular center called shadow and an enveloping luminous ring produced by the hot accretion disk surrounding the astrophysical object. In this chapter, we want to explain the basic tools to analyse the optical appearance of a compact object. Starting by the light bending near a massive body and the expected detected images when a star illuminates a black hole. Finally, we assume different models of accretions disks as well as the technique to obtain the similar images as the one obtained by the Einstein telescope.